2012
DOI: 10.1149/1.3702861
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Anode Electrode Materials for Cu-Cl/HCl Electrolyzers for Hydrogen Production

Abstract: Ceramic carbon electrodes (CCE) containing poly aminopropyl siloxane (PAPS) were fabricated by the sol-gel method. These CCEs have previously been shown to exhibit high performance towards the anode reaction of the electrolytic process used in the Cu-Cl thermochemical cycle for hydrogen production, with optimal performance being achieved at 36 wt% PAPS. Using cyclic voltammetry, electrochemical impedance spectroscopy, and scanning electron microscopy, the peak performance at 36 wt% PAPS was explained in terms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…They also quantified the kinetic parameters through electrochemical methods of characterization including linear sweep voltammetry (LSV), membrane conductivity and permeability measurements, durability testing of the membrane and preparation procedures for a membrane electrode assembly (MEA). Also, past studies were reported for CuCl/HCl(aq) electrolyzer performance at UOIT, including electrochemical analysis of the anolyte, 3 chemical exergy of the anolyte, 2 anode material improvement 6,7 and sensitivity analysis of different operating parameters on the MEA performance in actual operating conditions. 7 This paper develops a comprehensive model for a CuCl/HCl(aq) electrolyzer cell and stack.…”
Section: Symbolsmentioning
confidence: 99%
See 1 more Smart Citation
“…They also quantified the kinetic parameters through electrochemical methods of characterization including linear sweep voltammetry (LSV), membrane conductivity and permeability measurements, durability testing of the membrane and preparation procedures for a membrane electrode assembly (MEA). Also, past studies were reported for CuCl/HCl(aq) electrolyzer performance at UOIT, including electrochemical analysis of the anolyte, 3 chemical exergy of the anolyte, 2 anode material improvement 6,7 and sensitivity analysis of different operating parameters on the MEA performance in actual operating conditions. 7 This paper develops a comprehensive model for a CuCl/HCl(aq) electrolyzer cell and stack.…”
Section: Symbolsmentioning
confidence: 99%
“…Also, past studies were reported for CuCl/HCl(aq) electrolyzer performance at UOIT, including electrochemical analysis of the anolyte, 3 chemical exergy of the anolyte, 2 anode material improvement 6,7 and sensitivity analysis of different operating parameters on the MEA performance in actual operating conditions. 7 This paper develops a comprehensive model for a CuCl/HCl(aq) electrolyzer cell and stack. Previous theoretical and experimental studies for the CuCl/HCl (aq) electrolyzer focused on an individual cell performance in the absence of other existing cells in the stack.…”
Section: Symbolsmentioning
confidence: 99%
“…Overall reaction : The electrolysers that have been operated in earlier studies have mostly employed commercially available Pt/C electrocatalyst in the MEA at both cathode and anode. [28][29][30][31][32][33] The MEA production and its functioning are critical from the standpoint of CuCl/HCl electrolysis efficiency. Besides Pt/C, another Pt-based electrocatalyst that has also found promise in MEA is directly bonded Pt on membrane or platinized membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Commercial MEA's based on Pt/C electrocatalyst has been generally employed in reported literature. 43,47,[49][50][51][52][53][54] In our earlier study, we had employed a platinized Nafion membrane as MEA with electrocatalyst coated only on the cathode side. 48 In this study we prepare Pt/C electrocatalyst with varied Pt loadings and compare their electrochemical surface area (ECSA).…”
mentioning
confidence: 99%